Sustainability Analysis of Independent Palm Oil Plantations in Sintang Regency, West Kalimantan - Kamaludin, Kamaludin; Harisudin, Mohamad; Sutrisno, Joko; Irianto, Heru (Journal of International Conference Proceedings, 2023)
The goal of this investigation is to examine the impact of institutional, technological, social, and economic factors on the long-term viability of independent oil palm plantations in West Kalimantan's Sintang Regency. The data obtained from interviewing 216 respondents, spread across three sub-districts, namely, the Sintang, Kelam Permai, and Binjai Hulu; and used Multi-dimensional Scaling RAPFISH (Rapid Assessment Techniques for Fisheries) to analyze the data. The research results show that the sustainability index values in different aspects are generally favorable, such as the sustainability index value in the economic aspect is 74.36%, the value in the social aspect is 71.28%, the environmental value is 70.59%, the institutional dimension value is 72.34% and the technology dimension value is 70.14%. Considering the sensitive attributes of this research as decisive factors some efforts should be made to sustained the oil palm plantations. Furthermore, governments and policymakers should strengthen their institutional and organizational role in supporting oil palm plantations to make it easier for farmers to access technology, assistance with plantation facilities, and agricultural extension services.